Fungal Endophytic Communities of Two Wild Rosa Varieties With Different Powdery Mildew Susceptibilities - Zhao, Yi; Xiong, Zhi; Wu, Guangli; Bai, Weixiao; Zhu, Zhengqing; Gao, Yonghan; Parmar, Shobhika; Sharma, Vijay K.; Li, Haiyan (Frontiers in Microbiology, 2018)
Powdery mildew (PM) is one of the most devastating and wide spread fungal diseases of rose, which seriously decrease its productivity and commercial value. In the present study, the endophytic fungal communities of two wild Rosa varieties (Rosa multiflora Thunb and R. multiflora var. carnea Redouté and Thory) with different PM susceptibilities were studied through Illumina MiSeq sequencer. A total of 14,000,424 raw reads were obtained from 60 samples, and 6,862,953 tags were produced after merging paired-end reads. 4462 distinct OTUs were generated at a 97% similarity level. It was found that only 34.2% of OTUs shared between two plant varieties. All of the OTUs were assigned into four fungal phyla, 17 classes, 43 orders, 86 families, 157 genera, and 208 species. Members of Ascomycota were found to be the most common fungal endophytes (EF) among all plant samples (93.7% relative abundance), followed by Basidiomycota (4.7% relative abundance), while Zygomycota and Glomeromycota were found to be rare and incidental. At each developmental stage of plants, the diversity and community structure of EF between two Rosa varieties showed significant differences. Both PCoA plots and PERMANOVA analyses indicated that developmental stage was the major factor contributing to the difference between the Rosa varieties (R2 = 0.348, p < 0.001). In addition, plant varieties and tissues were also important factors contributing to the difference (R2 = 0.031, p < 0.05; R2 = 0.029, p < 0.05). Moreover, Neofusicoccum, Rhodosporidium, and Podosphaera, etc., were found to be significantly different between two Rosa varieties, and some of the endophytes may play a role in PM resistance. These finding are encouraging to testify the potential use of these fungi in the biocontrol of PM in future studies.